Rekrutmen, pengembangan, keterlibatan karyawan dalam kinerja perusahaan dimediasi oleh komitmen organisasi - Lim, Arvin; Fatyandri, Adi Neka (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The company's current challenge is to win the talent war, what is meant by talent war is where companies compete to beat their competitors and obtain the best talent in the labor market, this affects the company so that companies are more careful in selecting and developing existing talents. With talent management, this step in finding development talent management, grouping talented employees, and other retention programs is more integrated. In this study, the method used was a quantitative method, which examined the existing population, and was used as a sample from a small part of the population. Then the results were obtained that employee recruitment and selection have a significant positive effect on company performance with organizational commitment as a mediating variable for talented employee recruitment to assist the organization in obtaining talented employees, developing them, and retaining them so that they can contribute to advancing the company's performance.